Effective Minimization of Side Lobe Level of Sparse Thinned Planar Array Antenna in Multiple Planes with Constraints. Issue 5 (4th July 2021) - Dutta, Kailash Pati; Mahanti, G. K.; Panda, G.
ABSTRACT: In this paper, the authors propose to design thinned sparse planar array antenna in multiple planes using meta-heuristic optimization algorithm such as Teaching Learning-Based Optimization (TLBO) algorithm. The objective is to achieve the minimum value of side lobe level (SLL) in the radiation pattern in two vertical planes as well as in all vertical planes. The optimal positions of the isotropic antennas in the array are obtained having multiple optimization constraints such as total number of antennas in the array, aperture area and minimum inter-element spacing. The simulation results demonstrate that the proposed method is found to be relatively simpler but promising compared to the results reported using other competitive methods.